The unique antecedents of customer loyalty towards mobile service - Mah, Pei Yew (2017)
Customer loyalty has been highly sought topic to enable growth and competitiveness enhancement in current market situation. The increase of telecommunication sector in the country had influence mobile service providers competing with each other to become a major service provider. Specifically, there is an issue when the number of mobile cellular subscriptions and penetration rate in Malaysia had declined in the first quarter of 2017 compared to 2016. Customer loyalty is important in increasing profitability and continued survival in competitive market. There are limited studies conducted in Malaysia on customer loyalty towards mobile service providers. This study tries to fill the contextual gap by investigating the effects of independent variables and the mediating effects of satisfaction. Additionally, this study intends to investigate perceived quality, corporate image, perceived value, satisfaction that influence customer loyalty and perceived quality, corporate image, perceived value that influence satisfaction. It also aims to examine the influence of satisfaction as a mediator between perceived quality, corporate image, perceived value and customer loyalty. A total of 531 questionnaires were distributed and 431 questionnaires were obtained and usable. Partial Least Squares 2.0 (PLS) was used to analyze the data. The findings indicate that perceived quality does not influence customer loyalty, whereby corporate image, perceived value and satisfaction influence customer loyalty. Meanwhile, perceived quality, corporate image and perceived value also have strong relationship on satisfaction. Satisfaction also mediates the relationship between perceived quality, corporate image, perceived value and customer loyalty. The outcome of this study can be used by service providers to enhance and improve customer loyalty in the context of mobile service providers. The findings extend researchers’ understanding of predictors that influence customer loyalty in mobile service providers in Malaysia.